2018
DOI: 10.1194/jlr.m077222
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct lipid-lipid interactions in plasma and affected tissues in a diabetic mouse model

Abstract: Lipids are ubiquitous metabolites with diverse functions; abnormalities in lipid metabolism appear to be related to complications from multiple diseases, including type 2 diabetes. Through technological advances, the entire lipidome has been characterized and researchers now need computational approaches to better understand lipid network perturbations in different diseases. Using a mouse model of type 2 diabetes with microvascular complications, we examined lipid levels in plasma and in renal, neural, and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 59 publications
5
42
0
Order By: Relevance
“…In line with these findings, extensive lipid accumulation has been reported within kidney glomeruli and tubulointerstitium in individuals with type 2 diabetes who had diabetic kidney disease [63]. Moreover, using postmortem human retina samples, we recently obtained data suggesting alterations in lipid metabolism in retinas from donors with diabetic retinopathy (P. E. Fort, unpublished data), consistent with the reduction observed in BKS db/db mice [30]. The importance of these findings is highlighted by the observation that genetic deletion of the fatty acid synthase gene in the neuroretina leads to progressive neurodegeneration, with synaptic dysfunction, neuronal cell apoptosis and visual impairment [64].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationssupporting
confidence: 83%
See 4 more Smart Citations
“…In line with these findings, extensive lipid accumulation has been reported within kidney glomeruli and tubulointerstitium in individuals with type 2 diabetes who had diabetic kidney disease [63]. Moreover, using postmortem human retina samples, we recently obtained data suggesting alterations in lipid metabolism in retinas from donors with diabetic retinopathy (P. E. Fort, unpublished data), consistent with the reduction observed in BKS db/db mice [30]. The importance of these findings is highlighted by the observation that genetic deletion of the fatty acid synthase gene in the neuroretina leads to progressive neurodegeneration, with synaptic dysfunction, neuronal cell apoptosis and visual impairment [64].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationssupporting
confidence: 83%
“…To our knowledge, no other study has examined alterations in glucose metabolism across complications within the same animal model of diabetes. Besides this study, transcriptomic studies, in combination with metabolomic and proteomic analysis of tissues from both animal models of diabetes and human biopsies from diabetic individuals, have implicated both glucosedependent and independent mechanisms [26][27][28][29][30][31][32][33]. Using metabolomics analysis, Priyadarsini et al found no effect of glucose-derived metabolite flux in human corneal stroma of individuals with type 1 and type 2 diabetes [33].…”
Section: Mechanisms Of Onset and Progression Of Diabetic Complicationsmentioning
confidence: 80%
See 3 more Smart Citations